Distribution and its sighificance of the common pathogenic bacteria in teeth combined periodontal-endodontic lesions of periodontal origin - PAZILIBIEKE ·Jiangali; MAMUTI ·Mireayikezi; ZHAO Li; LU Hao (口腔疾病防治, 2022)
Objective To study the distribution of pathogenic infection and relevance in combined periodontal-endodontic lesions of periodontal origin,and provide the basis for clinical treatment. Methods Totally 43 cases of combined periodontal-endodontic lesions of periodontal origin from Jan. 2018 to Jun. 2020 treated in the hospital were selected, including a total of 43 teeth as the experimental group. Another 41 teeth from 41 cases with severe periodontitis during the same period were set as the control group. subgingival plaque samples and root canal samples of ill teeth were made for test. Quantitative Real-time PCR was used to detect the quantity of Tannerella forsythia (Tf), Porphyromonas gingivalis (Pg), Fusobacterium nucleatum (Fn), Prevotella intermedia (Pi), Treponema denticola (Td), Digestive streptococcus (Ds), Enterococcus faecalis (Ef), Porphyromanus endodontics (Pe). Results There was no significant difference in the quantity of Digestive streptococcus and Porphyromanus endodontics in the root canal tissue and subgingival plaque of the experimental group (Ρ>0.05), other six pathogenic bacteria in the subgingival plaque samples was significantly higher than that from the root canal tissue (P<0.05); No significant difference in the quantity of Digestive streptococcus was found in the subgingival plaque between the two groups (P=0.241). Other seven pathogenic bacteria in the subgingival plaque samples of the experimental group was significantly higher than that from the control group (P<0.05); The number of Ef, Pe, Pg, Td and Tf in the root canal tissue was closely related to the subgingival plaque in the experimental group, Ef (r=0.347, Ρ < 0.05), Pe (r=0.363, Ρ < 0.05), Pg (r=0.437, Ρ < 0.01), Td (r=0.471, Ρ < 0.01), Tf (r=0.679, Ρ < 0.01). Conclusion The quantity of common pathogenic bacteria in the root canal tissue of Combined periodontaI-endodontic lesions of periodontal origin was lower than that from the subgingival plaque sample, and the quantity of common pathogenic bacteria in the root canal tissue was closely related to the subgingival plaque. During clinical treatment, attention should be paid to the control of pulp tissue infection while controlling periodontal tissue infection.